Effect of Change in Geometry on Time Period of Lattice Parabolic Shells Using SAP2000 OAPI - Suwal, Rajan; Rajbhandari, Prayush (Journal of the Institute of Engineering, 2023)
Nowadays, shell structures are frequently used in various areas and are preferred by architects and structural engineers due to its aesthetics and efficient load carrying capacities. Shell structures, especially lattice shell structures, are commonly used in airports, malls, train station and stadium where aesthetics and larger span are of prime importance. Theses lattice shell structures are formed by arranging the structural element in a triangulated form and held together by fixed nodes which prevent it from local buckling. Lattice Shells provide the benefit of thin shell structures, yet overcomes the difficulties of casting, i.e., they do not need complicated formworks.